A STUDY ON THE OPPORTUNITY AND CONSTRAINTS FOR FOOD GRAINS PRODUCTION - RUBY KUMARI (International Journal of Multidisciplinary Research and Studies, 2020)
The state is classified as belonging to agroclimatic zone IV (Middle-Gangetic plain region). The remaining division of the state is into its three agro ecological zones. The average rainfall for the year is 1,764 millimetres, and the rainy season lasts from June to September. 5.67 million hectares were considered to be the "net" area that was planted, whereas 7.91 million hectares were considered to be the "gross" area that was farmed. The total cultivable land is 6.64 million hectares. The percentage of land used for agriculture was 139%. The consumption of fertiliser nutrients (N+P2O5+K2O) per hectare is 162.8 kg/ha. Irrigation is used on approximately 61.1% of the total net planted area. The total area that was irrigated in 2007-2008 was 4.79 million hectares, while the area that was irrigated on a net basis was 3.46 million hectares. The level of ground water development is only 39%, despite the fact that the annual replenishable ground water resource is 29.19 billion cubic metres (BCM), of which draught is 10.77 BCM.